Clinical Features Differ Between Patients With Vertigo Attack Only and Weakness Attack Accompanying Vertigo Before Vertebrobasilar Stroke: A Retrospective Study - Deng, Yalan; Zhang, Lei; Zhang, Rongsen; Duan, Jingfeng; Huang, Jiabing; Qiu, Dongxu (Frontiers in Neurology, 2022)
Objective: To determine the clinical features of patients with vertigo symptoms and weakness before vertebrobasilar ischemic stroke. Methods: In this 4-year retrospective study, we manually screened the medical records of 209 patients hospitalized with vertigo attack as the main complaint, who were finally diagnosed with acute vertebrobasilar ischemic stroke. Patients were divided into two groups according to the symptoms: patients who only had vertigo attack prior to vertebrobasilar stroke (vertigo attack group) and patients who had both vertigo and weakness attacks prior to the stroke (vertigo and weakness attack group). Clinical parameters, including infarction site and volume, relative risk factors, ABCD2 score, and medical intervention, were compared between the two groups. Results: The prevalence of hypertension was higher in the vertigo attack group (42.2% vs. 29.0%, P<0.05). The total cerebral infarction volume in the vertigo attack group was larger than the vertigo and weakness attack group (4.44 cm3 versus 2.12 cm3, p<0.05). Additionally, the cerebellum was more likely to be affected in the vertigo attack group. In contrast, patients in vertigo and weakness attack groups had higher carotid stenosis (14.2% vs. 27.2%, P< 0.05) and ABCD2 score (2.1 ± 1.2 vs. 3.6 ± 1.5, P=0.02). The percentage of medullary infarctions also increased in the vertigo and weakness attack groups. Vertigo attack events occurred more frequently in the vertigo and weakness attack groups (median 2.4 vs. 4.3, p<0.04). We also found that patients in the vertigo and weakness attack groups were more likely to seek medical intervention after vertigo. Conclusions: Clinical parameters, including infarction location, relative risk factors, and ABCD2 score were different between vertigo symptoms with and without weakness attacks. These findings highlight the clinical features of patients with vertigo and weakness attacks before vertebrobasilar ischemic stroke.